The Isometopinae (Hemiptera: Heteroptera: Miridae) of India and Sri Lanka: A Review of the Subfamily, with Descriptions of Six New Species - Yeshwanth, H.m.; Chérot, F.; Henry, T.j. (Zootaxa, 2021)
The subfamily Isometopinae (Insecta: Hemiptera: Heteroptera: Miridae) from India and Sri Lanka is reviewed. Nine genera and seventeen species are recorded from both countries, keyed, illustrated, and diagnosed. Six species are described as new: Astroscopometopus hesaraghattaensis, n. sp., Isometopus webbi, n. sp. and Isometopus wolskii, n. sp., Isometopidea viraktamathi, n. sp., Myiomma belavadii, n. sp., and Myiomma ramamurthyi, n. sp. Alcecoris periscopus McAtee and Malloch 1924, Isometopus yoshizawai Yasunaga & Duwal, 2006 and Paloniella parallela Yasunaga & Hayashi, 2002 are reported for the first time from India.